2018
DOI: 10.1111/pan.13509
|View full text |Cite
|
Sign up to set email alerts
|

The power of N‐PASS, aEEG, and BIS in detecting different levels of sedation in neonates: A preliminary study

Abstract: Summary Background Sedatives are essential drugs in every intensive care unit in order to ensure the patient's optimal level of comfort. Avoiding conditions of over‐ and under‐sedation is a challenge in a neonatal intensive care setting. Drug administration could be optimized by the concomitant use of objective methods to assess the level of sedation. Aims We aimed to look at the ability of different methods (Neonatal Pain, Agitation and Sedation Scale, amplitude‐integrated Electroencephalogram, and Bispectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
(90 reference statements)
1
14
0
Order By: Relevance
“…BIS has been found to correlate with sedation measured with the Ramsay sedation scale, the University of Michigan Sedation Scale) and the COMFORT Behavior scale . BIS is however less useful at identifying undersedation than it is oversedation and evidence is limited in younger infants, particularly in neonates, with low BIS values seen even with only light sedation . Given this limitation, we also incorporated pediatric efficacy data from a study of oral clonidine in infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BIS has been found to correlate with sedation measured with the Ramsay sedation scale, the University of Michigan Sedation Scale) and the COMFORT Behavior scale . BIS is however less useful at identifying undersedation than it is oversedation and evidence is limited in younger infants, particularly in neonates, with low BIS values seen even with only light sedation . Given this limitation, we also incorporated pediatric efficacy data from a study of oral clonidine in infants.…”
Section: Discussionmentioning
confidence: 99%
“…30 BIS is however less useful at identifying undersedation than it is oversedation and evidence is limited in younger infants, particularly in neonates, with low BIS values seen even with only light sedation. 31 Given this limitation, we also incorporated pediatric efficacy data from a study of oral clonidine in infants. This study cohort included neonates and…”
Section: Plasma Profiles Obtained Following Pk Simulationmentioning
confidence: 99%
“…Nine of the 29 studies reported use of the N-PASS sedation domain. Sedation was measured in extremely preterm (n = 5) [33][34][35][36]41], very preterm (n = 4) [33,36,41,42], late preterm (n = 6) [33,36,[40][41][42][43], and term infants (n = 5) [33,36,[40][41][42]. Sedation was measured in the NICU (n = 8) [33][34][35][36][40][41][42][43] and PACU setting (n = 1) [30].…”
Section: Sedationmentioning
confidence: 99%
“…Sedation was measured in extremely preterm (n = 5) [33][34][35][36]41], very preterm (n = 4) [33,36,41,42], late preterm (n = 6) [33,36,[40][41][42][43], and term infants (n = 5) [33,36,[40][41][42]. Sedation was measured in the NICU (n = 8) [33][34][35][36][40][41][42][43] and PACU setting (n = 1) [30]. N-PASS sedation domain was measured for mechanically ventilated (n = 8) [33][34][35][36][40][41][42][43], nonmechanically ventilated (n = 2) [34,36], and postoperative (n = 3) infants [30,33,41].…”
Section: Sedationmentioning
confidence: 99%
See 1 more Smart Citation